2007 IEEE International Parallel and Distributed Processing Symposium 2007
DOI: 10.1109/ipdps.2007.370239
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation and Evaluation of Client-Side File Caching for MPI-IO

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Data prefetching improves performance by overlapping application's data access phases and computation phases. The prefetching thread needs to predict what data the application will request and fetches the data from storage devices to local buffer (or a collective cache in parallel I/O system [10]) before the application issuing the actual requests.…”
Section: A Accurate and Timely Data Prefetchingmentioning
confidence: 99%
“…Data prefetching improves performance by overlapping application's data access phases and computation phases. The prefetching thread needs to predict what data the application will request and fetches the data from storage devices to local buffer (or a collective cache in parallel I/O system [10]) before the application issuing the actual requests.…”
Section: A Accurate and Timely Data Prefetchingmentioning
confidence: 99%
“…Such synchronization provides a collective I/O implementation an abundant opportunity for process collaboration, for instance, by exchanging access information and reorganizing the I/O requests. Many collaboration strategies besides the two-phase I/O and disk directed I/O have been proposed and demonstrated their successes, including server-directed I/O [18], persistent file domain [3,2], active bu鈫礶ring [13], and collaborative caching [4,11]. Independent I/O, in contrast, requiring no synchronization makes any collaborative optimization di cult.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Previous research efforts with parallel I/O on the Lustre file system have shed some light on factors contributing to the poor performance of MPI-IO, including the problems caused by I/O accesses that are not aligned on stripe boundaries [17,18]. Figure 3 helps to illustrate the problem that arises when I/O accesses cross stripe boundaries.…”
Section: A Known Issues With Parallel I/o On Lustrementioning
confidence: 99%
“…In [18], it was shown that aligning the data to be written with the basic striping pattern improves performance. They also showed that it was important to align on lock boundaries.…”
Section: Related Workmentioning
confidence: 99%